2020
DOI: 10.1016/j.schres.2020.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral complement proteins in schizophrenia: A systematic review and meta-analysis of serological studies

Abstract: Background There is renewed focus on the complement system in the pathogenesis of schizophrenia. In addition to providing aetiological insights, consistently dysregulated complement proteins in serum or plasma may have clinical utility as biomarkers. Methods We performed a systematic literature review searching PubMed, Embase and PsycINFO for studies measuring complement system activity or complement protein concentrations in serum or plasma from patients with schizophr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 94 publications
(217 reference statements)
1
26
0
Order By: Relevance
“…In circulation, the complement system interacts with pathogens to mark them for destruction by phagocytes 45 . The literature regarding findings in patients with SZ is inconclusive: while some studies have shown increased peripheral complement protein concentration in patients with SZ 46 , 47 , a recent meta-analysis has concluded that the evidence regarding complement system dysregulation is mixed 48 . In addition, recent evidence has suggested that the complement cascade is involved in several central nervous system processes, including neurogenesis and synaptic pruning, and has specifically been implicated in SZ 49 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…In circulation, the complement system interacts with pathogens to mark them for destruction by phagocytes 45 . The literature regarding findings in patients with SZ is inconclusive: while some studies have shown increased peripheral complement protein concentration in patients with SZ 46 , 47 , a recent meta-analysis has concluded that the evidence regarding complement system dysregulation is mixed 48 . In addition, recent evidence has suggested that the complement cascade is involved in several central nervous system processes, including neurogenesis and synaptic pruning, and has specifically been implicated in SZ 49 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…This is also consistent with our results, as C4-ana is an in vivo by-product of C4 protein activation. Furthermore, several studies observed increased levels of a C4 protein inhibitor, C4-binding protein, in individuals with schizophrenia, implying an active compensatory mechanism [ 13 , 27 ]. Together, these findings suggest that plasma C3-ana may play a role in acute psychosis, whereas plasma C4-ana may contribute in a more chronic manner.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy individuals, peripheral blood C4A and C4B protein concentrations correlate with the C4A and C4B gene copy number but also depend on age and sex [ 31 , 32 ]. The literature on the serological complement system in schizophrenia is large but characterized by small samples, variable methodological approaches, clinical diversity of cohorts, failure to assay C4A and C4B separately in most studies, and inconsistent results [ 2 , 3 , 27 ]. A recent meta-analysis of 10 studies of C4 protein concentration (mostly in serum) included 468 individuals with schizophrenia and 440 controls.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis compared plasma complement protein levels and activity between SCZ patients and HC. Pooled estimated means did not reveal differences between the two groups in 11 studies of C3 and 10 studies of C4, even though individual studies reported significant increases in C3 and C4 in SCZ compared to HC [ 23 ]. Two more recent studies (not included in the meta-analysis) added to these inconsistencies.…”
Section: Microglial Synaptic Pruningmentioning
confidence: 99%